2014
DOI: 10.1111/desc.12245
|View full text |Cite
|
Sign up to set email alerts
|

The brain adapts to orthography with experience: evidence from English and Chinese

Abstract: Using functional magnetic resonance imaging (fMRI), we examined the process of language specialization in the brain by comparing developmental changes in two contrastive orthographies: Chinese and English. In a visual word rhyming judgment task, we found a significant interaction between age and language in left inferior parietal lobule and left superior temporal gyrus, which was due to greater developmental increases in English than in Chinese. Moreover, we found that higher skill only in English children was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 74 publications
2
34
0
Order By: Relevance
“…We also found that, at a slightly different location, English showed greater activation than Chinese in bilateral STG regardless of task. These regions have been found to be related to phonological representation and orthography-phonology-conversion [63] with stronger phonological activation in English L1 reading than Chinese L1 reading in the superior temporal gyrus [7]. Our results are consistent with this language difference in STG found in previous studies and add that it occurs for writing as well as reading.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found that, at a slightly different location, English showed greater activation than Chinese in bilateral STG regardless of task. These regions have been found to be related to phonological representation and orthography-phonology-conversion [63] with stronger phonological activation in English L1 reading than Chinese L1 reading in the superior temporal gyrus [7]. Our results are consistent with this language difference in STG found in previous studies and add that it occurs for writing as well as reading.…”
Section: Discussionsupporting
confidence: 91%
“…Chinese-English comparisons have been found in visuo-orthographic regions (more involved in Chinese reading) and phonological regions (more involved in English reading) [7]. For example, bilateral superior parietal lobules, middle occipital gyri and fusiform gyri show more activation in Chinese reading, whereas left inferior frontal gyrus, superior temporal gyrus and inferior parietal lobule are more involved in English reading [3].…”
Section: Introductionmentioning
confidence: 99%
“…Given its importance, developmental cognitive neuroscience has investigated how different regions of the human cerebral cortex develop their specificity during reading acquisition (Turkeltaub, Gareau, Flowers, Zeffiro, & Eden, ; Turkeltaub, Eden, Jones, & Zeffiro, ). A traditional approach towards understanding the neural underpinnings of reading development has been to investigate the change in activation level of particular local brain regions (Cao et al, ; Cao, Brennan, & Booth, ; Price, ; Szaflarski et al, ; Turkeltaub et al, ). For example, a previous English study reported a developmental decrease in the activation of the dorsal part of the left superior temporal gyrus in a visually presented word rhyming judgment task (Bitan et al, ), indicating that there was reduced reliance on phonology in English reading development.…”
Section: Introductionmentioning
confidence: 99%
“…As for Chinese reading, a similar developmental trend has been found. For example, Cao et al (2009Cao et al ( , 2010Cao et al ( , 2015 reported that adults showed greater activation than children in the right middle occipital gyrus on reading tasks, suggesting that adults more effectively engage the brain region involved in visual-orthographic processing of Chinese characters, while children showed greater activation than adults in the left superior temporal gyrus in a rhyming task, suggesting children rely more on phonological representations of Chinese words (Cao et al, , 2010(Cao et al, , 2015.…”
mentioning
confidence: 99%
“…That is, Norwegian orthographic to phonological mappings are fairly consistent and can be used to correctly pronounce unfamiliar words while mappings in English are not as consistent. The difference in consistency may result in differences in reading network use throughout development (Cao, Brennan, & Booth, 2015; Levy et al, 2009; Seghier et al, 2008). …”
Section: Introductionmentioning
confidence: 99%